Epigenetics and the Human Brain: Where Nurture Meets Nature - Mansuy, Isabelle M. (The Dana Foundation, 2011)
While our genetic code determines a great deal of who and what we are, it does not act alone. It depends heavily on the epigenome, an elaborate marking of the DNA that controls the genome’s functions. Because it is sensitive to the environment, the epigenome is a powerful link and relay between our genes and our surroundings. Epigenetic marks drive biological functions and features as diverse as memory, development, and disease susceptibility; thus, the nurture aspect of the nature/nurture interaction makes essential contributions to our body and behaviors. As scientists have learned more about how the epigenome works, they have begun to develop therapies that may lead to new approaches to treating common human conditions.